The Role of Traditional Plant Knowledge in the Fight Against Infectious Diseases: A Meta-Analytic Study in the Catalan Linguistic Area - Gras, Airy; Parada, Montse; Vallès, Joan; Garnatje, Teresa (Frontiers in Pharmacology, 2021)
Infectious diseases represent, as a group, the main cause of mortality in the world. The most important reasons are multidrug resistant pathogens, the rapid spread of emerging diseases aggravated by globalization, and the extended reach of tropical and vector-borne diseases resulting from continued climate change. Given the increase in these diseases and the limited effectiveness of antibiotics, traditional knowledge can constitute a useful tool to address these new health challenges. The aim of this work is to analyse extensively the available ethnobotanical data linked to infections and infestations in the Catalan linguistic area, with the intention of depicting the panorama of the folk use of herbal products to address the quoted ailments, preserving the popular plant knowledge and management data. The meta-analytic work performed in the present paper covers 29 research studies belonging to different regions throughout the Catalan linguistic area. The medicinal ethnoflora to treat infections and infestations in the Catalan linguistic area includes 326 taxa belonging to 78 botanical families of vascular plants. The informant consensus factor (FIC) was 0.92 and the ethnobotanicity index (EI) was 7.26%. Artemisia absinthium (10.98%; 0.37) and Thymus vulgaris (8.06%; 0.27) are the most quoted taxa and have the highest values of the cultural importance index. The most reported use was the antihelminthic (30.15%), followed by the internal antiseptic (19.43%) and antipyretic (13.69%). The medicinal importance index shows the relevance of the antihelminthic use (14.23), but also the use against measles (10.19). The information is coincidental with at least one of the comprehensive pharmacological literature sources checked for 47.42% of ethnobotanical uses. These results, centred on the plants used to treat infection and infestation diseases, are the first step towards selecting some of the most interesting species to develop phytochemical and pharmacological studies and suggesting an alternative regarding how to face the health emergency involving the expansion of infectious diseases, based on local and traditional knowledge.